Scientometric Evaluation of Research on Bioceramics - Kim, Jong-Heon; Noh, Kyung-Ran; Kwon, Oh-Jin; Choi, Sung-Bae; Kil, Sang-Cheol (Asian Journal of Chemistry, 2014)
During the past several years, there has been a major advance in the development of biomedical materials including various ceramic materials for skeletal repair and reconstruction. To understand bioceramics research trends, we investigated total 12,157 research papers published from 2003 to 2012. These research papers were published by 100 countries. The bioceramics research had steadily increased each year. The bioceramics research trends had expanded from hydroxyapatite to hydroxyapatite, calcium phosphate and titania for the last 10 years.